Mengurangi Kemiskinan Melalui Zakat di Aceh - Abdul Rani Usman; Cut Nazarina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to analyze the role of zakat in reducing extreme poverty in Aceh, focusing on the distribution of zakat to poor asnaf during the month of Ramadan 2022. Zakat, as the third pillar of Islam, has a strategic function in creating social balance and eradicating poverty. In the context of Aceh, the management of zakat is carried out by Baitul Mal Aceh (BMA), which is in charge of collecting and distributing zakat in accordance with Islamic sharia principles and government regulations. This research approach uses a qualitative descriptive method with literature study, reviewing official reports, academic literature, and statistical data. The results of the study show that the mechanism of zakat distribution by BMA is carried out through verification in each village, by identifying two poor people as beneficiaries. The zakat distributed has a significant impact in meeting the basic needs of the poor and reducing extreme poverty. However, there are challenges in the distribution of zakat and infaq funds that have not been fully distributed until the end of the year, which requires strategic steps to prevent inflation and maintain economic stability in Aceh. Zakat has great potential as a solution to alleviate extreme poverty in Aceh. Synergy between BMA, the government, and related institutions is needed to ensure more effective and sustainable zakat management.